2004
DOI: 10.1084/jem.20041196
|View full text |Cite
|
Sign up to set email alerts
|

Primary HIV-1 Infection Is Associated with Preferential Depletion of CD4+ T Lymphocytes from Effector Sites in the Gastrointestinal Tract

Abstract: Given its population of CCR5-expressing, immunologically activated CD4 ϩ T cells, the gastrointestinal (GI) mucosa is uniquely susceptible to human immunodeficiency virus (HIV)-1 infection. We undertook this study to assess whether a preferential depletion of mucosal CD4 ϩ T cells would be observed in HIV-1-infected subjects during the primary infection period, to examine the anatomic subcompartment from which these cells are depleted, and to examine whether suppressive highly active antiretroviral therapy cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
742
1
18

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 983 publications
(791 citation statements)
references
References 40 publications
30
742
1
18
Order By: Relevance
“…Several months later, those authors reported significantly increased levels of circulating LPS in both chronically HIV-infected individuals and SIV-infected rhesus macaques (RM) that positively correlated with measures of innate and adaptive immune activation (33). After that initial report, numerous studies have confirmed that HIV infection is associated with a substantial loss of CD4 ϩ T cells residing in the gut, in turn leading to microbial translocation (34,35).…”
Section: Definition Of Microbial Translocationmentioning
confidence: 88%
“…Several months later, those authors reported significantly increased levels of circulating LPS in both chronically HIV-infected individuals and SIV-infected rhesus macaques (RM) that positively correlated with measures of innate and adaptive immune activation (33). After that initial report, numerous studies have confirmed that HIV infection is associated with a substantial loss of CD4 ϩ T cells residing in the gut, in turn leading to microbial translocation (34,35).…”
Section: Definition Of Microbial Translocationmentioning
confidence: 88%
“…During early infection, the cell destruction involves primarily CCR5+ effector memory T cells and occurs predominantly in the mucosal tissue, particularly in the intestinal immune system [15,16]. Disordered apoptosis and an increased rate of activation-induced cell death (AICD) lead to destabilization and progressive change of the homeostasis of resting naive and memory T cell populations [14,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to distinguish naïve and memory subsets in macaques led to the discovery that simian immunodeficiency virus rapidly and selectively infects and eliminates "memory" CD4+ T cells, particularly in mucosal tissues [1][2][3], findings that were recently confirmed in HIV-infected patients [4,5]. These findings have revolutionized our understanding of HIV pathogenesis by demonstrating that HIV *Corresponding author: RS Veazey, Tulane National Primate Research Center, 18703 Three Rivers Road, Covington, LA 70433, Phone (985) 871-6228, Fax (985) 871-6510, Email: rveazey@tulane.edu.…”
Section: Introductionmentioning
confidence: 99%